Frequency of Th17 CD20+ cells in the peripheral blood of rheumatoid arthritis patients is higher compared to healthy subjects - Eggleton, Paul; Bremer, Edwin; Tarr, Joanna M; de Bruyn, Marco; Helfrich, Wijnand; Kendall, Alexandra; Haigh, Richard C; Viner, Nick J; Winyard, Paul G (Arthritis research & therapy, 2011)
Introduction Rheumatoid arthritis (RA) is considered a T cell driven autoimmune disease, therefore, the ability of B cell depleting biologics, e.g., anti-CD20 antibodies, to alleviate RA is unclear. This study examined the proportions of IL-17-secreting lymphocytes in the blood of healthy subjects and RA patients and determined if Th17 cells belong to a CD20+ subset of T cells. Methods Fluorescence-activated cell sorting and confocal microscopy verified CD3, CD4/CD8 and CD20-staining of T cells. IL-17 secretion was determined using a commercial assay. Results In healthy subjects and RA patients blood, the median percentage of total CD20+ lymphocytes was similar (7.5%; n = 6 and 10.3%; n = 9, respectively) and comprised predominantly of B cells (~ 86%). However, 2-4% of CD3+ T cells from both healthy subjects ( n = 7) and RA ( n = 8) individuals co-expressed CD20. The peripheral blood of healthy subjects contained few IL-17-secreting CD20+ T cells (< 0.1%; n = 6). In contrast, in RA blood a median and interquartile range % of, 24.2%; IQR 28.5 of IL-17-secreting T cells were CD20+ ( n = 9; p = 0.02). Conclusions In the blood of RA patients, a greater proportion of Th17 cells are of a CD20+ phenotype compared to healthy individuals. These cells may represent an additional target for anti-CD20 therapies.